Comparing linguistic symmetries: Teachers and students analyze Spanish and English in the classroom Comparando simetrías lingüísticas: Estudiantes y docentes analizan el español y el inglés en el aula - Fernando Rodríguez-Valls (Arizona State University, 2009)
This article analyzes the impact of a teaching methodology of English based on the investigation and comparative analysis conducted by students and teachers of sentences constructed in Spanish and spoken in English. Second-generation Hispanic students 'born in the US' who are learning English in the public schools of California; utilize the grammar of two languages on a daily basis. Yet, the activities utilized to teach and evaluate these students oftentimes do not analyze in an explicit way sentences that mix two languages. The model described in this article was implemented during the 2005-2006 school year with 29 Hispanic students enrolled in fourth grade in a public school of Los Angeles. The outcomes of this project suggest that students, who, guided by the teachers, analyze the connections between the two languages using a comparative method, not only perform extremely well in the state exams but also develop a vision of these two languages as codes with linguistic symmetries that create a communal block of knowledge. Este trabajo analiza el impacto de una metodología de enseñanza del inglés basada en la investigación y el análisis comparativos por parte de alumnos y maestros de oraciones construidas en español y expresadas en inglés. Estudiantes hispanos de segunda generación —nacidos en Estados Unidos— que aprenden inglés en las escuelas públicas de California utilizan a diario la gramática de dos lenguas, sin embargo, las actividades que se utilizan para enseñar y evaluar a estos alumnos a menudo no analizan de una manera explícita oraciones que mezclan dos lenguas. El modelo propuesto en este artículo se puso en práctica con un grupo de veintinueve estudiantes hispanos de cuarto grado de una escuela pública de Los Ángeles, durante el curso escolar 2005-2006. Los resultados obtenidos sugieren que los alumnos que analizan, guiados por los maestros, las relaciones y conexiones entre las dos lenguas de una manera comparativa no solamente consiguen excelentes resultados en los exámenes del estado sino que también desarrollan una percepción de las dos lenguas como códigos con simetrías lingüísticas que ayudan a crear un bloque común de conocimiento.